Population-based rapid assessment of avoidable blindness survey in Sohag governorate in Egypt. Issue 10 (12th October 2020) - AlSawahli, Heba; McCormick, Ian; Mpyet, Caleb D; Ezzelarab, Gamal; Shalaby, Mohammad
Abstract : Objectives: To determine the prevalence and causes of blindness and vision impairment, and the coverage and quality of cataract surgical services, among population aged 50 years and older in Sohag governorate in Egypt. Design: A population-based cross-sectional survey using two-stage cluster random sampling following the rapid assessment of avoidable blindness methodology. Setting: A community-based survey conducted by six teams of ophthalmologists, assistants and local guides. Enrolment and examination were door-to-door in selected clusters. Participants: Using 2016 census data, 68 population units were randomly selected as clusters (of 60 people) with probability proportionate to population size. Anyone aged 50 years and older, residing in a non-institutional setting in a cluster for at least 6 months, was eligible to participate. Primary and secondary outcome measures: The prevalence and causes of blindness and vision impairment. Secondary outcomes were CSC and effectiveness and participant-reported barriers to cataract surgery. Results: Of 4078 participants enrolled, 4033 (98.9%) were examined. The age-adjusted and sex-adjusted prevalence of blindness, severe vision impairment and moderate vision impairment were 5.9% (95% CI 4.8% to 6.9%), 4.7% (95% CI 3.8% to 5.7%) and 18.9% (95% CI 16.8% to 21.0%), respectively. Cataract caused most of blindness (41.6%), followed by non-trachomatous corneal opacity (15.7%) and posterior segment diseases (14.5%). Cataract surgical coverage (CSC) for persons for visual acuity <3/60 was 86.8%, the proportion of cataract surgeries with poor visual outcome was 29.5% and effective CSC (eCSC) was 44.9%. eCSC was lower in women than men. The most frequently reported barrier to surgery was cost (51.5%). Conclusions: The prevalence of blindness in Sohag governorate is higher than districts in other middle-income countries in the region. CSC was high; however, women suffer worse quality-corrected CSC than men. The quality of cataract surgery needs to be addressed, while health system strengthening across government and private settings could alleviate financial barriers.